2020
DOI: 10.3389/fmicb.2020.00615
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diversity and Mycotoxins in Low Moisture Content Ready-To-Eat Foods in Nigeria

Abstract: Low moisture content ready-to-eat foods vended in Nigerian markets could be prepackaged or packaged at point of sale. These foods are widely and frequently consumed across Nigeria as quick foods. Despite their importance in the daily diets of Nigerians, a comprehensive study on the diversity of fungi, fungal metabolite production potential, and mycotoxin contamination in the foods has not yet been reported. Therefore, this study assessed the diversity of fungi in 70 samples of low moisture content ready-to-eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 104 publications
8
24
2
Order By: Relevance
“…In addition, averantinmethylether (9.4 µg/kg) and aspergillimide (21.3 µg/ kg) are two uncommon compounds found only in cultures of one strain of A. aflatoxiformans and A. flavus, respectively. Similar to a recent report (Ezekiel et al 2020), two of the four A. flavus strains, examined in this study, produced sporogen AO1 (mean: 974 µg/kg), confirming the production of this compound in A. flavus. One of the four A. flavus strains, DTO 421-G6, did not produce aflatoxins, any of its pathway metabolites, cyclopiazonic acid or kojic acid, but produced cyclosporins A, B, C and H. Cyclosporin production has been reported in Aspergillus terreus (Sallam et al 2003), Neocosmospora solani (Sawai et al 1981) and Tolypocladium (El-Enshasy et al 2008).…”
Section: Aspergillus Metabolitessupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, averantinmethylether (9.4 µg/kg) and aspergillimide (21.3 µg/ kg) are two uncommon compounds found only in cultures of one strain of A. aflatoxiformans and A. flavus, respectively. Similar to a recent report (Ezekiel et al 2020), two of the four A. flavus strains, examined in this study, produced sporogen AO1 (mean: 974 µg/kg), confirming the production of this compound in A. flavus. One of the four A. flavus strains, DTO 421-G6, did not produce aflatoxins, any of its pathway metabolites, cyclopiazonic acid or kojic acid, but produced cyclosporins A, B, C and H. Cyclosporin production has been reported in Aspergillus terreus (Sallam et al 2003), Neocosmospora solani (Sawai et al 1981) and Tolypocladium (El-Enshasy et al 2008).…”
Section: Aspergillus Metabolitessupporting
confidence: 92%
“…A. fijiensis) liberated several known extrolites: aspergillimide (mean: 30.1 mg/kg), emodin (mean: 541 µg/ kg), endocrocin (mean: 23 mg/kg), iso-rhodoptilometrin (mean: 340 µg/kg), meleagrin (mean: 7.6 mg/kg), oxaline (mean: 17.3 mg/kg), paraherquamide E (mean: 6 mg/kg) and secalonic acid D (mean: 64.7 mg/kg) (Varga et al 2011, Vesth et al 2018). However, citreorosein and tryprostatin B, two compounds recently reported to be produced by A. brunneoviolaceus from garri (farinated cassava) in Nigeria (Ezekiel et al 2020), were not detected in cultures of the present strains. Nonetheless, six uncommon compounds (aurasperon C, dimethylsulochrin (mean: 1.9 mg/kg), fellutanine A (152 µg/kg), methylorsellinic acid (mean: 1.2 mg/kg), nigragillin and pyrophen (mean: 190 µg/kg)) were produced by strains examined in the present study.…”
Section: Aspergillus Metabolitescontrasting
confidence: 63%
“…Previously, we had shown the presence of aflatoxin M 1 in melon (Ezekiel et al 2016 ). Although these metabolites were previously regarded as products of endogenous biotransformation of aflatoxin B 1 by CYP450 enzyme, they are now detectable in food crops (Warth et al 2012 ; Adetunji et al 2014 ; Ogara et al 2017 ; Oyedele et al 2017 ; Ezekiel et al 2020b ); thus, suggesting possible release of and exogenous activity of the CYP enzymes by aflatoxigenic fungi during food storage.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, both toxins were found in 12% of the sesame samples at mean concentrations of 6 and 4 μg kg −1 , respectively, which contrasts a recent report that did not find both toxins in 35 sesame samples collected in 2013 from markets in Nasarawa state (Ogara et al under review ). The disparity in the contamination data for sesame may be attributed to climate actions (especially increased rainfall that brings about increased moisture levels) and/or improved sensitivity of the analytical method as recently, citrinin is now commonly found in foodstuffs in Nigeria (Ojuri et al 2018 ; Ezekiel et al 2020b ). Similarly, low levels of both toxins were reported in melon (Somorin et al 2016 ) and sesame (Ezekiel et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although CIT/DHC was not detected in the examined complementary foods in the present study it was found in 74% of the urines of EB children. CIT levels in grains (especially maize) and complementary food in Nigeria have recently been shown to be high reaching 16,000 µg/kg (Okeke et al 2015, 2018; Ojuri et al 2018, 2019; Ezekiel et al 2020). Fermented cocoa beans in Nigeria, which could also be processed and used in the preparation of foods for infants and young children, have also recently been reported to contain CIT (Akinfala et al 2020).…”
Section: Resultsmentioning
confidence: 99%